Microbiological Surveillance of Peritoneal Dialysis Associated Peritonitis: Antimicrobial Susceptibility Profiles of a Referral Center in GERMANY over 32 Years - Kitterer, Daniel (PLoS One, 2015)
OBJECTIVES: Peritonitis is one of the most important causes of treatment failure in peritoneal dialysis (PD) patients. This study describes changes in characteristics of causative organisms in PD-related peritonitis and antimicrobial susceptibility. METHODS: In this single center study we analyzed retrospective 487 susceptibility profiles of the peritoneal fluid cultures of 351 adult patients with peritonitis from 1979 to 2014 (divided into three time periods, P1-P3). RESULTS: Staphylococcus aureus decreased from P1 compared to P2 and P3 (P<0.05 and P<0.01, respectively). Methicillin-resistant S. aureus (MRSA) occurred only in P3. Methicillin-resistant Staphylococcus epidermidis (MRSE) increased in P3 over P1 and P2 (P <0.0001, respectively). In P2 and P3, vancomycin resistant enterococci were detected. The percentage of gram-negative organisms remained unchanged. Third generation cephalosporin resistant gram-negative rods (3GCR-GN) were found exclusively in P3. Cefazolin-susceptible gram-positive organisms decreased over the three decades (93% in P1, 75% in P2 and 58% in P3, P<0.01, P<0.05 and P<0.0001, respectively). Vancomycin susceptibility decreased and gentamicin susceptibility in gram-negatives was 94% in P1, 82% in P2 and 90% in P3. Ceftazidim susceptibility was 84% in P2 and 93% in P3. CONCLUSIONS: Peritonitis caused by MSSA decreased, but peritonitis caused by MRSE increased. MRSA peritonitis is still rare. Peritonitis caused by 3GCR-GN is increasing. An initial antibiotic treatment protocol should be adopted for PD patients to provide continuous surveillance.